2022
DOI: 10.7759/cureus.20981
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cholecystitis Presenting With Septic Shock as the First Presentation in an Elderly Patient

Abstract: Gangrenous cholecystitis (GC), a severe complication of acute cholecystitis, is associated with higher morbidity and mortality rates than uncomplicated cholecystitis. In this report, we present the case of an 81year-old female with diabetes mellitus and hypertension who presented in the emergency department complaining of severe generalized abdominal pain for 10 days. The pain was associated with nausea and vomiting. She had septic shock, prompting admission, and was eventually diagnosed with perforated GC. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…The causes of a partial response to antibiotic therapy consist of three aspects: the antibiotic, the target pathogen, and the patient’s body system. These aspects include the bacterial status, inoculum size, antibiotic concentrations, serum effects, and host-gut microbiome interactions [ 11 ]. However, we ruled out these hypotheses because K. ozaenae was not detected in the later cultures and because the second chest CT revealed that opacity in the lower left lung zone had improved.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of a partial response to antibiotic therapy consist of three aspects: the antibiotic, the target pathogen, and the patient’s body system. These aspects include the bacterial status, inoculum size, antibiotic concentrations, serum effects, and host-gut microbiome interactions [ 11 ]. However, we ruled out these hypotheses because K. ozaenae was not detected in the later cultures and because the second chest CT revealed that opacity in the lower left lung zone had improved.…”
Section: Discussionmentioning
confidence: 99%
“…La CA es una de las consecuencias más comunes de colelitiasis, que ocurre principalmente debido a la obstrucción del conducto cístico por cálculos impactados [21,22] . El desarrollo de cambios secundarios en el contexto de la CA, como gangrena, inflamación xantogranulomatosa, hemorragia y enfisema, define la CA grave [21,23] .…”
Section: Discussionunclassified
“…A, Vesícula distendida de 15x8x6cm gangrenada en cuerpo y bacinete, conteniendo en su interior coágulos organizados color rojo oscuro, y múltiples cálculos, el mayor de 15mm. B,C,D y E, Salida de contenido vesicular (coágulos y cálculos) durante la colecistectomía laparoscópica CG [25] ; y el factor de riesgo más prevalente es la diabetes mellitus, la cual se asocia a poli-neuropatía, lo cual puede enmascarar el cuadro [22,25] .…”
Section: Discussionunclassified
“…The mortality rate of severe biliary infections ranges from 1% to 6%, reaching 10-20% when combined with bacteremia. This is crucial, especially in the elderly, in which bacteremia following the biliary tract infection is the second most frequent cause of sepsis [10,11].…”
Section: Introductionmentioning
confidence: 99%